Operations Strategy of Chinese Textile Industry: Fulfilment of Market Requirement - Bai, Luping (2007)
Purpose: The purpose of this paper is to study the major operations strategies in Chinese textile manufactories based on HUADA and IMILI case studies. In addition, a supply chain partner selection model is introduced in discussion part to evaluate the supplier of IMILI. At the same time, Chinese "Guanxi" factor is discussed by using this model.